The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s10995-015-1849-0
|View full text |Cite
|
Sign up to set email alerts
|

Low-Level Symptoms of Depression in Mothers of Young Children are Associated with Behavior Problems in Middle Childhood

Abstract: Children whose mothers experience low-level depressive symptoms early in their development have increased risk for later behavioral problems, suggesting a possible need for new screening and intervention strategies for mothers with lower than clinically elevated symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 40 publications
5
32
0
3
Order By: Relevance
“…Numerous studies have addressed an increased risk of behavioral problems in children of depressed mothers (Araya et al, 2009;Brennan et al, 2000;Campbell et al, 2009;Civic and Holt, 2000;Conners-Burrow et al, 2015;Fihrer et al, 2009;Josefsson and Sydsjö, 2007;Korhonen et al, 2014). A meta-analysis of 193 studies found an increased risk for internalizing and externalizing problems as well as general psychopathology in children of depressed mothers, although effects were small (Goodman et al, 2011).…”
Section: Maternal Depression and Depressive Symptomsmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have addressed an increased risk of behavioral problems in children of depressed mothers (Araya et al, 2009;Brennan et al, 2000;Campbell et al, 2009;Civic and Holt, 2000;Conners-Burrow et al, 2015;Fihrer et al, 2009;Josefsson and Sydsjö, 2007;Korhonen et al, 2014). A meta-analysis of 193 studies found an increased risk for internalizing and externalizing problems as well as general psychopathology in children of depressed mothers, although effects were small (Goodman et al, 2011).…”
Section: Maternal Depression and Depressive Symptomsmentioning
confidence: 99%
“…While many studies have focused on clinically diagnosed depression, a recent study indicated that even subclinical levels of maternal depressive symptoms have a negative effect on child behavior (Conners-Burrow et al, 2015).…”
Section: Maternal Depression and Depressive Symptomsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is growing evidence for long-term negative effects of even subclinical depressive symptoms on children's well-being 2. Given the low rates of treatment for women with elevated depressive symptoms and the long-term sequelae of untreated depression, there is a need to develop effective preventive INTs.…”
Section: Contextmentioning
confidence: 99%
“…Mothers’ negative feelings and emotional disturbance have been documented from this perspective. Many of these scientific studies about mothers tend to focus on their negative psychological states and/or poor role performance, the respective causes, and predicting factors (Skipstein et al, 2012; O’Hara and McCabe, 2013; Taylor and Johnson, 2013; Tyrlik et al, 2013; Highet et al, 2014; Jover et al, 2014; Agrati et al, 2015; Razurel and Kaiser, 2015; Meier et al, 2016; Tikotzky, 2016; Kim et al, 2017), as well as the consequences it entails for the child’s behavior, development, and well-being (Herba et al, 2013; O’Hara and McCabe, 2013; Jover et al, 2014; Spijkers et al, 2014; Yürümez et al, 2014; Betts et al, 2015; Fairbrother et al, 2015; Junttila et al, 2015; Conners-Burrow et al, 2016; Riva Crugnola et al, 2016; Woolhouse et al, 2016; Granat et al, 2017; Moed et al, 2017). Specific groups, such as teenage mothers (Smith et al, 2017), mothers who experienced preterm labor (Karabekiroglu et al, 2015), or mothers of children who have been clinically diagnosed as disabled (Loukisas and Papoudi, 2016), also arouse scientific curiosity, and are viewed as an abnormal phenomenon, in comparison to normative mothers, assumed as control groups.…”
Section: Introductionmentioning
confidence: 99%